APPROACHES TO USING PEDAGOGICAL TECHNOLOGIES IN TEACHING UZBEK LANGUAGE - Sayyora Xolmirzayeva (American Journals, 2023)
This article explains that in teaching the Uzbek language, students' literacy in the field of speech in the field of life and work can be achieved through a map of perception, which is further expanded and adapted to the specialty. Scientists have commented on the theoretical foundations of the concept map, its history, its advantages in the teaching process, and its rules of development. The article is intended for teachers and specialists from all walks of things.
Keywords: innovation, pedagogical technology, perception map, foreign experience, industry, tradition, national values, association, thinking.